Odpowiedzi

2010-03-01T18:53:00+01:00
A) = 5x kwadrat - 2
b) = 3x kwadrat - 1

niewiem czy dobrze ;p
2010-03-01T18:56:04+01:00
A) 6x² - x - 2 =0
Δ = b² - 4ac
Δ = (-1)² - 4*6*(-2)
Δ = 1+48
Δ = 49
√Δ = 7

x₁ = (-b-√Δ) / 2a = (1-7) / 2*6 = -6 / 12 = - ½
x₂ = (-b-√Δ) / 2a = (1+7) / 2*6 = 8 / 12 = ⅔

/ - > kreska ułamkowa

b) 2x² + x - 1 <0
Δ = b² - 4ac
Δ = (1)² - 4*2*(-1)
Δ = 1+8
Δ = 9
√Δ = 3

x₁ = (-b-√Δ) / 2a = (-1-3) / 2*2 = -4 / 4 = -1
x₂ = (-b-√Δ) / 2a = (-1+3) / 2*2 = 2/ 4 = ½

/ - > kreska ułamkowa
rozwiązaniem jest zbiór (-1 ; ½)